Crest Center for Non-invasive Rehabilitation and Sensory Therapy - Ladia, Jana Gabrielle J. (College of Architecture, University of the Philippines Diliman, 2019)
The Center for Non-Invasive Rehabilitation and Sensory Therapy or CREST, located in Tanay, Rizal, specializes on light and vibroacoustic therapies in curing both mental and physical illnesses while incorporating the importance of nature in the well being of a person. CREST is an avenue for holistic activities aimed for the betterment of the general public without the need for medical intervention. CREST offers facilities and amenities that take advantage of natural environment with a stunning view of the Sierra Madre Mountain Range behind the facility. The use of natural light and nature sounds to enhance the overall ambiance of the place was a design feature used to enhance the general effect of the building on the user's health.